(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The concurrent use of Hibiscus sabdariffa and drugs for the treatment of various ailments is a common practice amongst patients; a practice that could result in drug-herb interaction. Objective: To evaluate the effects of Hibiscus sabdariffa water extract on the pharmacokinetics of lisinopril. Methodology: The study involved 24 apparently healthy humans randomly selected and divided into two groups of 12 each. Study was carried out in four phases as crossover study with a washout period of two weeks between the phases; Group 1 (received lisinopril 10 mg alone), group 2 (received lisinopril 10 mg with 200 mL Hibiscus sabdariffa calyxes water extract (25 mg/mL) concurrently), group 2 (received lisinopril 30 min after administration of Hibiscus sabdariffa water extract) and group 1 (received Hibiscus sabdariffa water extract 30 minutes after administration of lisinopril). Saliva samples collected at 0.5 to 36.0 hr in each phase were analysed for lisinopril content using a developed and validated RP-HPLC method. Results were analysed using one-way Anova followed by Tukey’s post Hoc. Results: Lisinopril administered alone (group 1) achieved Cmax of 95.36 ng/mL at 7 hr (Tmax). Slight increases in Cmax of lisinopril were observed when the drug was interacted with Hibiscus sabdariffa in groups 2 (97.50 ng/mL), 3 (97.37 ng/mL) and 4 (99.24 ng/mL) respectively. The of lisinopril alone was 736805.83 ng.hr/mL. The corresponding for group 2, 3 and 4 are 800409.29, 816866.47, and 10450.03 ng.hr/mL respectively. However, these increases in Cmax and seen were not statistically significant (p < 0.05). Pharmacokinetic parameters were computed using Kinetica software. Conclusion: Hibiscus sabdariffa calyxes water extract (200 mL of 25 mg/mL) does not significantly affect the pharmacokinetics of lisinopril in healthy humans.